Morbidity from primary glaucoma and its gender-specific aspects amongst the population of Siberian industrial town - A. L. Onischenko; A. V. Kolbasko; N. M. Zhilina; A. V. Zacharova; A. E. Vlasenko (Oftalʹmologiâ)
Aim: To analyze visual morbidity attributable to primary glaucoma, its eight-year dynamics, and gender differences in Siberian industrial town inhabitants.Methods: Medical records (out-patient and in-patient departments) from the database of the sectional information analysis center of Novokuznetsk Health Administration over an eight-year period (2004-2011) were studied. Individual patients diagnosed with primary glaucoma in 2004‑2011 were reviewed only.Results: Standardized primary glaucoma morbidity rate in men and women aged over 40 years was 3.5±0.3 ‰ and 2.6±0.26 ‰, respectively. Men were diagnosed with primary glaucoma earlier than women. In male residents aged over 70 years, primary glaucoma was found more often than in female residents. Male glaucoma patients required in-patient treatment more often than female patients. Primary glaucoma was diagnosed in men and women at 66.1±11.6 and 67.0±10.9 years (on average), respectively (U = 2.27, p = 0.023). 441 of 5424 patients (8.1 %) diagnosed with glaucoma in 2004‑2011 subsequently died. The average age at death was 69.0±7.2 years, the median (25 %; 75 %) was 71 years (66 years; 75 years). Patients who were diagnosed with primary glaucoma survived for 2.6±1.8 years. The median (25 %; 75 %) was 2 years (1 year; 4 years). The distribution of the variable that characterized the difference between the age at death and the age of diagnosis making was abnormal (D = 0.151, p<0.001). Half of glaucoma patients died in the first two years after glaucoma has been diagnosed. Less than 20 % of patients (16 % men, 18 % women) survived for ≥4 years after primary glaucoma diagnosis has been made. Conclusion: The analysis of morbidity and mortality rates as well as disability due to impaired vision is of great importance to health official and practitioners. Stably low glaucoma morbidity rate in Siberian industrial town inhabitants indicates a great lack of glaucoma specialists and forces to develop optimal organizational arrangements as well as observational and treatment approaches to glaucoma care.